2017
DOI: 10.5539/ijms.v9n5p108
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Luxury Value Perception and Shopping Motivations: Turkey Sample

Abstract: It was aimed to reveal the effects of financial, functional, individual and social value perceptions on hedonic and utilitarian shopping motivations within this study. In this direction, a questionnaire was conducted to people over the age of 18 in cities representing 12 regions of Turkey and 2857 questionnaires were put into consideration in total. Confirmatory factor analysis and structural equation modelling (SEM) were applied to data. According to findings it was identified that the luxury value perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This result is consistent with research conducted by Al-hajla (2017) indicated a significant relationship between symbolic values and luxury consumption behavior including purchase intentions. Respondents of present research explain the similarity of socially conscious consumers as discussed byKurnaz (2017) andGupta (2017). Attaining the services with a value that makes the millennial convey the impression of high standards Enlightening Tourism.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This result is consistent with research conducted by Al-hajla (2017) indicated a significant relationship between symbolic values and luxury consumption behavior including purchase intentions. Respondents of present research explain the similarity of socially conscious consumers as discussed byKurnaz (2017) andGupta (2017). Attaining the services with a value that makes the millennial convey the impression of high standards Enlightening Tourism.…”
mentioning
confidence: 84%
“…While considering the social values, consumers tend to consider their social status, image, and desires and refer to the products, which can raise prestige and identity (Wu & Chang, 2016). Consumers get opportunities to articulate their identities by using luxury services and products (Kurnaz, 2017). Such symbolic, conspicuousness is further been found to influence attitude towards the luxury products and services among people especially Indian consumers (Berthon et al, 2009;Han et al, 2010;Wu & Chang, 2016;Kurnaz, 2017;Gupta, 2017).…”
Section: 3) Social Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Dubois and Duquesne (1993) noted that luxury brands employed simple branding strategies (such as Vogue advertisements) and established shops in prime locations, like Fifth Avenue in New York. But the luxury market has grown immensely over the last decade (Ciornea et al, 2012;Wiedmann et al, 2009;Kurnaz, 2017), and evidently luxury products are more widely available to consumers than ever before (Kapferer & Bastien, 2012). Furthermore, the global luxury industry is going through two interesting trends from: a) physical product to digital experiential and b) standardization to personalization (Deloitte, 2017).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%